Delayed development influences the outcome of different grades of D5 and D6 blastocysts during freeze–thaw cycle - Zhang, Huina; Arhin, Samuel Kofi; Zhao, Junzhao; Hou, Xiaohong; Chen, Yilu; Huang, Zhaoxia (Cellular and Molecular Biology, 2019)
To analyze the effects of blastocysts on the 5th day (D5) and 6th day (D6) of frozen–thawed blastocyst transplantation on pregnancy outcome and provide evidence for further improvement of the strategy. This study included transfers from the Reproductive Medicine Center of the Second Affiliated Hospital of Wenzhou Medical University during freeze–thaw cycles from January 2016 to December 2017. They were divided into D5 group (1616 cases) and D6 group (619 cases) according to blastocyst formation and development. Each group was further divided into 5 groups according to the quality of the blastocyst and the number of transplants, making a total of 10 groups. Following the frozen transplantation cycle, the transplanting rate was significantly higher for D5 (41.73%) than for D6 (23.98%) (P < 0.05); the ongoing pregnancy rate (47,40%) was also significantly higher than that of D6 (28.43%) (P < 0.05).In the frozen–thawed blastocyst resuscitation transplantation, compared to D6 blastocysts, D5 blastocysts were more conducive to blastocyst implantation and could be used to achieve better clinical pregnancy outcome. In blastocyst selection, a single D5 excellent blastocyst transplant is preferred. Only at the 6th day of non-excellent D6, 2 blastocysts are recommended for transplantation.